The multilevel effect of marketing activities on sales, revenue and profitability in a micro-enterprise - Barreiros Porto, Rafael; da Rocha Costa, Rafaela; Alberto de Morais Watanabe, Eluiza (Review of Business Management, 2017)
Purpose – This study dynamically assessed the effectiveness of marketing activities in the generation of product sales, revenue, and profitability in a micro-enterprise, a context that lacks research in marketing. Design/methodology/approach – A longitudinal multilevel study was conducted using daily panel data for 5,800 products sold and monthly time series on the business level, involving 26 months of commercial and financial records for a micro-enterprise (a drugstore). Panel and time series regressions were performed. Findings – The research shows that (1) marketing activities, in particular price elasticity, quite accurately generate product sales, (2) the aggregated estimate of total marketing activities predicts monthly company revenue and profitability, and (3) in the investigated company, if marketing activities are intensified in the same proportion to increase costs in products and goods, they are not efficient in generating profit. Originality/value – This research supports investigations concerning micro-macro level analysis relationships with commercial and financial data in order to merge marketing decisions to finance.